Perturbation of the mucosa-associated anaerobic gut microbiota in streptozotocin-induced diabetic rats - Wirth, Roland; Bódi, Nikolett; Szalai, Zita; Chandrakumar, Lalitha; Maróti, Gergely; Kovács, Kornél L; Bagi, Zoltán; Mezei, Diána; Balázs, János; Bagyánszki, Mária (Acta Biologica Szegediensis, 2021)
Our aim was to map the gut region-specific diﬀerences of the mucosa-associated microbiome distribution in a streptozotocin-induced diabetic rat model. Tissue samples from the duodenum, ileum and colon were collected 10 weeks after the onset of hyperglycaemia to analyse the mucosa-associated microbiota using next-generation DNA sequencing. Striking diﬀerences were observed in the mucosa-associated microbiota of the duodenum between diabetic and control rats. A significant invasion of the aerobic genus Mycoplasma was apparent in diabetes, and the abundance of the anaerobic phylum Firmicutes decreased massively. It is noteworthy that insulin treatment eliminated the Mycoplasma invasion in the duodenum and apparently restored the anaerobic environment in the mucosa. In the ileum the abundance of the phylum Firmicutes increased in the diabetic samples. Although the proportion of the phylum Proteobacteria decreased moderately, its composition changed significantly, and insulin treatment induced only minor alterations. In the diabetic samples of colon, the abundance of the phylum Firmicutes decreased slightly, the relative number of the bacteria in the phylum Bacteroidetes increased strongly as compared to the control values, and after insulin treatment this increase was more significant. Chronic hyperglycaemia has the most prominent eﬀect on the mucosa-associated microbiota in the duodenum.